Cold-atom-dimer reaction rates with He 4, Li 6,7, and Na 23 COLD-ATOM-DIMER REACTION RATES with He 4, ... SHALCHI, YAMASHITA, FREDERICO, and TOMIO - Shalchi, M. A. [UNESP]; Yamashita, M. T. [UNESP]; Frederico, T.; Tomio, Lauro [UNESP] (American Physical Society (APS), 2020)
Atom-dimer exchange and dissociation reaction rates are predicted for different combinations of two He4 atoms and one of the alkaline species among Li6, Li7, and Na23, by using three-body scattering formalism with short-range two-body interactions. Our study was concerned with low-energy reaction rates in which the s-, p-, and d-wave contributions are the relevant ones. The He4 is chosen as one of the atoms in the binary mixture, in view of available previous investigations and laboratory accessibilities. Focusing on possible experimental cold-atom realizations with two-atomic mixtures, in which information on atom-dimer reaction rates can be extracted, we predict the occurrence of a dip in the elastic reaction rate for colliding energies smaller than 20 mK, when the dimer is the He4Na23 molecule. We are also anticipating a zero in the elastic p-wave contribution for the He4+He4Li7 and He4+He4Na23 reaction processes. With weakly bound molecules reacting with atoms at very low colliding energies, we interpret our results in the light of Efimov physics which supports model independence and robustness of our predictions. Specific sensitivities on the effective range were evidenced, highlighted by the particular inversion role of the p- and d-waves in the atom exchange and dissociation processes.